Understanding the Efficacy of Bhutan’s First Ever Certificate Course in Social Work - Ramesh Kumar Chhetri; Sangay Wangchuk (Asian Social Work Journal, 2021)
With the transition of political, economic and social scenario in Bhutan, the Civil Society Organizations (CSOs) have been expanding over the years. Bhutan has more than forty registered CSOs and the numbers are still growing. However, paucity of trained social workers in Bhutan has compelled the CSOs to recruit employees with varying degrees. To mitigate this, Samtse College of Education (SCE) of the Royal University of Bhutan (RUB) launched Bhutan’s first ever certificate course in social work. So far, two cohorts of participants have been trained. This study was designed to understand the efficacy of Bhutan’s first ever certificate course in social work from the vantage point of the participants. It adopted a convergent parallel mixed method design, primarily employing questionnaires and semi-structured individual interviews. The study found the certificate course to be highly effective in enhancing the professional competence of the social workers in Bhutan. It is believed to have been an “eye-opening experience” for most social workers who ventured into this profession, without relevant training. The study recommends SCE and RUB to provide similar certificate courses to the thousands to untrained social workers in Bhutan.